The Relationship Of Peer Support With Student Self-Adjustment - Rahmadini Monika; Dina Sukma (Universitas Negeri Padang, 2021)
Self-adjustment is the individual's ability to deal with changes in the environment and in it there is an effort to achieve a harmonious relationship between environmental demands and the demands that exist within the individual. Self-adjustment is influenced by peer environmental factors. This study aims to look at the description of students 'self-adjustment, peer social support, and to examine the relationship between peer social support and students' adjustment. The study population was students of SMP Negeri 7 Bukittinggi, amounting to 440 people, with a sample of 210 students, selected by stratified random sampling. The results of this study indicate: (1) peer social support is in the high category, (2) adjustment is in the high category, (3) there is a relationship the positive significant between peer social support with adjustment.